1992
DOI: 10.1111/j.1699-0463.1992.tb00881.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinct stratum corneum antigen in psoriasis and its reactions with stratum corneum autoantibodies

Abstract: Qutaishat, S. S., Kumar, V., Beutner, E. H. & Jablonska, S. A distinct stratum corneum antigen in psoriasis and its reactions with stratum corneum autoantibodies. APMIS 100: 341-346, 1992. Stratum corneum antibodies are ubiquitous and can be detected by various immunological methods. Of these, the ones detected by hemagglutination undergo changes in antibody titers and have been implicated in psoriasis. The purpose of our study was to examine if differences exist in the activities of the antigens isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[58] It has been shown via the mixed agglutination technique on tissue sections that 25 patient's psoriatic lesions contained immunoglobulins of the IgG and IgM classes in the epidermis. The authors estimated the maximum immunoglobulin concentrations were around the dermal-epidermal junction, and above the dermal papillae.…”
Section: Discussionmentioning
confidence: 99%
“…[58] It has been shown via the mixed agglutination technique on tissue sections that 25 patient's psoriatic lesions contained immunoglobulins of the IgG and IgM classes in the epidermis. The authors estimated the maximum immunoglobulin concentrations were around the dermal-epidermal junction, and above the dermal papillae.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is tempting to speculate that a CIDAMP‐based, persisting epithelial defence reaction within the stratum corneum and stratum granulosum towards virulent C. simulans could eventually result in the generation of CIDAMP‐like autoantigens. Since CIDAMPs are generated from cationic IDP(R)s, which are highly abundant in keratinocytes, 37 and are produced within the fully differentiated epidermal layers, it would be plausible to see CIDAMP‐directed immune reactions, such as IgG‐deposits, within the stratum corneum 3,66 and autoreactive T‐cell‐mediated 67,68 responses within the stratum granulosum. Keratinocyte‐derived CIDAMPS as autoantigens would also help to explain the typical gyrate, demarcated lesion morphology of annular psoriasis, 69 where I would propose that the centre is missing CIDAMP sources due to a loss of the stratum granulosum.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in a small study using serum from five 18‐month‐old infants, we found that between ∼30% and 50% of skin‐like particles in their bed dust eluted antigens that bound their IgG (unpublished observations). Indeed, there is a long history of observations in this area [33–36]. Extracts of normal SC have been demonstrated to contain undescribed T cell antigens of high potency but limited structural diversity [37]; these appear to be analogous in effect to superantigens but require MHC Class II presentation.…”
Section: Immune Responses To Human and Animal Dandermentioning
confidence: 99%